Effect of Embedment on Generated Bending Moment in Raft Foundation under Seismic Load (Journal of Engineering, 2020)
This research shows the experimental results of the bending moment in a flexible and rigid raft foundation rested on dense sandy soil with different embedded depth throughout 24 tests. A physical model of dimensions (200mm*200mm) and (320) mm in height was constructed with raft foundation of (10) mm thickness for flexible raft and (23) mm for rigid raft made of reinforced concrete. To imitate the seismic excitation shaking table skill was applied, the shaker was adjusted to three frequencies equal to (1Hz,2Hz, and 3Hz) and displacement magnitude of (13) mm, the foundation was located at four different embedment depths (0,0.25B = 50mm,0.5B = 100mm, and B = 200mm), where B is the raft width. Generally, the maximum bending moment decreased with increasing the embedment depth from zero to B, by (75%,41%, and 43%) for the flexible raft under (1, 2 and 3) Hz respectively, for the rigid raft the maximum bending moment decreased by (62%, and 37%) under (1and 2) Hz respectively, for 3Hz excitation frequency, the direction of behavior wasn't the same for the case of the rigid raft foundation as the maximum bending moment increased with increasing the embedment depth from zero to (0.25B,0.5B and B) by (142% , 268% and 5%) compared with the surface raft foundation.